A Survey on the Current Status of Ophthalmological Consultations in Patients With Diabetes Undergoing Maintenance Hemodialysis and the Effectiveness of Education on Consultation Behavior –Experience of a Single Hemodialysis Clinic in Japan - Kimura, Moritsugu; Toyoda, Masao; Saito, Nobumichi; Abe, Makiko; Kato, Eri; Sugihara, Akemi; Ishida, Naoto; Fukagawa, Masafumi (Frontiers in Clinical Diabetes and Healthcare, 2022)
【Introduction】 It is extremely important for diabetic patients undergoing maintenance hemodialysis (MHD) to receive regular ophthalmologic examinations. However, even in the field of MHD in Japan, where there are many hemodialysis patients and the survival rate is said to be one of the highest in the world, we often see diabetic patients who do not receive regular ophthalmologic examinations. In this study, we surveyed the status of ophthalmology consultations and the use of diabetic eye notebook (DEN) among hemodialysis patients with diabetes at hemodialysis clinics to confirm the current situation, with the aim of confirming the effectiveness of education on consultation behavior by medical care staff. 【Materials and Methods】 This study included 38 diabetic hemodialysis patients attending one MHD clinic in Japan for one year from March 2018 to March 2019. In the first fact-finding survey in March 2018, hemodialysis care unit nurses (HCUNs) in the hemodialysis unit asked the diabetic hemodialysis patients whether they had consulted an ophthalmologist and used the DEN. Based on the results, the HCUNs recommended that hemodialysis patients with complications of diabetes be educated about the usefulness of regular ophthalmologic examinations, even during MHD, and that they use the DEN. This was followed by a second fact-finding survey in March 2019 to reconfirm ophthalmology consultations and DEN use. 【Results】 Regarding the presence of ophthalmology consultations, 22 of 38 (58%) patients had regular ophthalmology consultations in March 2018, and 27 of 38 (71%) patients had consultations in the following year after receiving information from an HCUN. Only 1 of 22 patients (5%) who consulted the ophthalmologist in March 2018 used a DEN, but 19 of 27 patients (70%) used it the following year. 【Conclusion】 In the future, the development and utilization of a new DEN that includes more detailed patient information, and the spread of self-care guidance to patients by multidisciplinary health care professionals, will increase the consultation rate of MHD patients in Japan and reduce the incidence and progression of ocular diseases in MHD patients.